The Concept of Normatizing the Expiry Period of the Job Loss Insurance Program (JKP) for Workers from the Perspective of Justice Theory - Sabrina, Novia Kusuma; Yahman, Yahman; Patrianto, Bangun (PT ARRUS Intelektual Indonesia, 2025)
The Job Loss Guarantee Program (JKP) is a social protection instrument for workers who experience termination of employment. However, the regulation of the 6-month expiry period for JKP benefit claims as stipulated in Government Regulation Number 6 of 2025 raises issues of justice, especially for workers facing industrial relations disputes or limited administrative access. The purpose of this study is to analyze how the concept of normalizing the expiry period for Job Loss Guarantee Program (JKP) claims in Indonesian laws and regulations is based on the principles of justice theory. This research method uses a normative juridical method with a statutory and conceptual approach. The results of the study indicate that the regulation of the expiry period for JKP claims emphasizes administrative legal certainty but does not fully reflect distributive justice for workers as the most disadvantaged group. Therefore, a more proportional and equitable reformulation of the JKP claim expiry period norm is needed to guarantee the protection of workers' constitutional rights.